PENGARUH PIJAT WOOLWICH (RANGSANGAN PADA PAYUDARA) TERHADAP PRODUKSI ASI PADA IBUPOST PARTUM DI BPM IRMA SUSKILAKECAMATAN MEDAN MARELANKOTA MADYA MEDAN TAHUN 2022 - Relinawaty Sinaga; Ninsah Mandala Putri Br Sembiring (Jurnal Medika Husada, 2022)
Increasing milk production in post partum mothers can be done by giving the mother a relaxing sensation to stimulate the hormones prolactin and oxytocin by doing Woolwich massage. This study aims to determine the effect of woolwich massage on milk production in post partum mothers at BPM Irma Suskila, Medan Marelan District, Medan Madya City in 2022. The population in this study were all post partum mothers who were at BPM Irma Suskila as many as 30 people. Sampling was taken using total sampling technique with a total sample of 30 respondents, 15 people in the intervention group and 15 people in the control group. The results obtained There is a comparison between giving woolwich massage to breast milk production in post partum mothers in the experimental group and the control group at BPM Irma Suskila with a p value of 0.002 or <0.05 with a z count value of 3.957 > z table 0.4394.